2002
DOI: 10.1046/j.1523-1747.2002.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Epidermal Protein-Bound ω-Hydroxyceramides in Atopic Dermatitis

Abstract: Atopic dermatitis is a common skin disease of unknown etiology with an impaired permeability barrier function. To learn more about the molecular pathology in lesional skin, we analyzed levels of free extractable as well as protein-bound barrier lipids in the epidermis of atopic dermatitis subjects. The amount of protein-bound omega-hydroxyceramides in healthy epidermis comprised 46-53 wt% of total protein-bound lipids, whereas this percentage was decreased to 23-28 wt% in nonlesional areas and even down to 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 65 publications
4
163
0
2
Order By: Relevance
“…1A), as extensively reported previously. 9,17,18 The total Cer in group LE was higher than that in group CA, and was similar to that in group C, which is consistent with our previous reports. 9 Cer bearing structural moieties of amide-linked non-hydroxy acid, a-hydroxy acid, or x-hydroxy acid as well as esterlinked fatty acid (FA) on sphingoid bases are critical to FIG.…”
Section: Epidermal Levels Of Cer Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…1A), as extensively reported previously. 9,17,18 The total Cer in group LE was higher than that in group CA, and was similar to that in group C, which is consistent with our previous reports. 9 Cer bearing structural moieties of amide-linked non-hydroxy acid, a-hydroxy acid, or x-hydroxy acid as well as esterlinked fatty acid (FA) on sphingoid bases are critical to FIG.…”
Section: Epidermal Levels Of Cer Speciessupporting
confidence: 91%
“…In AD, the decreased levels of Cer, GlcCer, or SM parallel the reductions in de novo Cer synthesis, the SMase activity, and/or the ceramidase activity. 18,23,24 Moreover, a deficiency of GlcCer synthase or SM synthase, enzymes involved in GlcCer or SM synthesis, respectively, results in significant reductions of GlcCer and/or SM, ultimately decreasing Cer levels. 10,25 Alternatively, unusual expression of SM deacylase, which metabolizes SM to sphingosyl phosphorylcholine, could also underlie the decreased levels of Cer in the epidermal lesions of AD patients.…”
mentioning
confidence: 99%
“…The skin surface of atopic individuals is often colonized by S. aureus, and an inverse correlation has been demonstrated between the free sphingosine level and the quantitative carriage of S. aureus in this condition (60). It has been noted that the level of covalently bound v-hydroxyceramides is reduced in the stratum corneum of atopic individuals (76). This may reflect the action of a ceramidase on the covalently bound v-hydroxyceramides to release free sphingoid bases and to leave behind v-hydroxyacids attached to the cornified envelope.…”
Section: Lipids As Part Of the Innate Immune Systemmentioning
confidence: 99%
“…It has been shown that extracellular ceramides and complex sphingolipids play important roles in forming the permeability barrier of skin (24). Macheleidt et al (27) showed that very long chain ceramides are reduced significantly in the epidermis of atopic dermatitis patients, suggesting that the very long chain ceramides have an important role in regulating the permeability barrier function. maCER1 may have a role in regulating the barrier function by regulating the levels of very long chain ceramides in skin.…”
Section: Figmentioning
confidence: 99%